2018
DOI: 10.1136/bmjopen-2017-019979
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of unplanned pregnancy in HIV-positive and HIV-negative pregnant women in Cape Town, South Africa: a cross-sectional study

Abstract: ObjectivesPrevention of unplanned pregnancy is a crucial aspect of preventing mother-to-child HIV transmission. There are few data investigating how HIV status and use of antiretroviral therapy (ART) may influence pregnancy planning in high HIV burden settings. Our objective was to examine the prevalence and determinants of unplanned pregnancy among HIV-positive and HIV-negative women in Cape Town, South Africa.DesignCross-sectional analysis.SettingsSingle primary-level antenatal care clinic in Cape Town, Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 28 publications
5
54
2
1
Order By: Relevance
“…Further, in the subset cohort of HIV‐infected women followed longitudinally through delivery, we found that high GWG was associated with increased risk of spontaneous PTD and HBW infants. In a country with both a high prevalence of obesity in women of child‐bearing age [11] and a high prevalence of HIV in pregnant women [39], our findings highlight the need for weight management interventions before and during pregnancy to minimise adverse birth outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…Further, in the subset cohort of HIV‐infected women followed longitudinally through delivery, we found that high GWG was associated with increased risk of spontaneous PTD and HBW infants. In a country with both a high prevalence of obesity in women of child‐bearing age [11] and a high prevalence of HIV in pregnant women [39], our findings highlight the need for weight management interventions before and during pregnancy to minimise adverse birth outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…A plausible explanation for this is that in a marital union there are open communication channels between the two individuals and this facilitates open discussion on reproductive-related issues like child-bearing and contraceptive use. Studies done elsewhere 15,16,31 also documented that WLH in a relationship were most likely to use contraception if there was open partner discussion among married couples. These communication channels 23 and South Africa 12,24,31 , demonstrate similar results.…”
Section: Discussionmentioning
confidence: 98%
“…Studies done elsewhere 15,16,31 also documented that WLH in a relationship were most likely to use contraception if there was open partner discussion among married couples. These communication channels 23 and South Africa 12,24,31 , demonstrate similar results. Our study also found that experiencing a higher number of pregnancies increased the likelihood of experiencing unintended pregnancy among WLH.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, over 70% of women who knew their HIV positive conceived on ART. This high fertility intention among women who started ART before a pregnancy was also demonstrated among HIV positive women in the Western Cape Province of South Africa [25]. Furthermore, women with pre-pregnancy ART entered ANC with higher immunological status compared to women who were undiagnosed or diagnosed but not on ART before the most recent pregnancy, but this difference faded at the end of the pregnancy.…”
Section: Discussionmentioning
confidence: 56%